1998
DOI: 10.1071/a97106
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationships between dietary ractopamine,energy intake, and sex in pigs

Abstract: A major constraint to protein deposition in the pig is energy intake. Ractopamine (RAC) isa b-agonist which has been shown to increase protein deposition under both ad libitum and restrictive feeding regimes. To assess the interactions between energy intake, sex, and dietary RAC, 104 crossbred pigs (52 boars and 52 gilts) were used in a slaughter-balance experiment conducted over the growth phase of 60-90 kg liveweight. To obtain initial body composition, 4 pigs of each sex were slaughtered at 60 kg. The remai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
29
0
4

Year Published

2005
2005
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 21 publications
10
29
0
4
Order By: Relevance
“…The studies that have shown no difference in lysine requirement have often been conducted with individually penned pigs where the full feed intake potential can be expressed and sometimes, in these cases, entire males may consume more feed than gilts (Dunshea et al, 1998;King et al, 2004). However, in commercial conditions, the ad libitum feed intake of entire males is well below that seen when entire males are penned in individual pens and slightly less than gilts (Dunshea, 2005).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The studies that have shown no difference in lysine requirement have often been conducted with individually penned pigs where the full feed intake potential can be expressed and sometimes, in these cases, entire males may consume more feed than gilts (Dunshea et al, 1998;King et al, 2004). However, in commercial conditions, the ad libitum feed intake of entire males is well below that seen when entire males are penned in individual pens and slightly less than gilts (Dunshea, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…The slope of the relationship between energy intake and protein deposition is steeper for entire males than for gilts or barrows (Campbell et al, 1985;Quiniou et al, 1996;Dunshea et al, 1998;King et al, 2004). Although older data suggest that, in finisher pigs, a plateau in protein deposition was achieved in all genders at an intake of around 33 to 42 MJ DE/day (Campbell et al, 1985;, studies conducted with genetically improved pigs suggest that the plateau occurs at higher feed intakes or, in the case of elite entire males, not at all (Rao and McKracken 1992;Dunshea et al, 1998;King et al, 2004).…”
Section: Lysine Requirements Of Immunocastrated Pigsmentioning
confidence: 98%
See 1 more Smart Citation
“…Este resultado está de acordo com DUNSHEA et al (1998) que não constataram interação entre níveis de energia digestível (21,2; 24,7; 28,2; 32,7; 36,7MJ dia -1 e a vontade) e a inclusão de 20ppm de ractopamina sobre o desempenho de suínos em terminação.…”
Section: Resultsunclassified
“…It is well established that the fatty acid composition of body fat reserves reflects that of the diet (Huo et al, 2003), and that fat deposition, in both pregnant and non-pregnant animals, is increased with increasing energy intake (Dunshea et al, 1998;Revell et al, 1998). Since maternal fat reserves are mobilised during late gestation and lactation (Mullan and Williams, 1990;Whittemore, 1998;Trottier and Johnston, 2001), it seems probable that the fatty acid composition of maternal fat reserves may have consequences for piglet growth and survival (Cieslak et al, 1983;Rooke et al, 2001b and c).…”
Section: Introductionmentioning
confidence: 99%